Caracterización de pacientes con colangitis diagnosticada mediante colangiopancreatografía retrógrada endoscópica en el Hospital Universitario San Rafael de Tunja - Barreto Noratto, Clara Patricia; Limas Solano, Luis Manuel; Aguilar Hernandez, Dajhanna Carolina; Inagan Quemá, Alexandra; Lopez Rivera, Ricardo Andres; Martinez Velasco, Andres Santiago (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2024)
Introduction: Cholangitis is a clinical syndrome characterized by jaundice, fever, and abdominal pain whose main cause is bile duct obstruction due to the presence of gallstones, which promotes bacterial growth. The main diagnostic method is the clinical presentation of the disease, and if it is not treated quickly int the first 24 hours, the patient´s survival may be compromised. Materials and Methods: A retrospective cross-sectional descriptive study was conducted, where the electronic medical records of patients undergoing ERCP at the San Rafael Hospital in Tunja during the period from 2020 to 2022 in whom the presence of cholangitis was endoscopically detected were analyzed. Results: A total of 70 patients were analyzed, the sex distribution was equal. The most frequent cause of obstruction was choledocholithiasis in 68.57% of cases, the average time of evolution was 7 days, being higher in patients from rural areas with 9 days. The most common comorbidity was hypertension (42,6%). The average surgical time was 34 minutes. In addition, 96.7% of patients received antibiotic treatment. Complications were infrequent, occurring in only 13,1% of the studied population. Post-ERCP mortality rate was 8.2%, occurring more frequently in patients over 80 years old. Conclusions: In our department the most frequent cause for the development of cholangitis is choledocholithiasis, with longer access time to ERCP to people coming from rural areas.